Pengelolaan Surat Masuk dan Keluar dalam Meningkatkan Penataan Kearsipan Madrasah Tsanawiyah Univa Medan - Alyani, Filza; Puspita, Dhea (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The research was conducted on Jl. SM Raja, Km. 5, 5, Harjosari 1 Village, Medan Amplas District. The aim is to describe what the management of incoming and outgoing mail looks like in improving the archival management of Madrasah Tsanawiyah Univa Medan. By conducting interviews with the Head of the Madrasah. Current developments in the field of technology are increasing, requiring an organization or educational institution to use a computerized system. Madrasah Tsanawiyah Univa Medan handles several letters every day from various parties such as research letters from students, letters from official offices, letters from foundations and other letters that are official and formal in nature. Research Methodology uses data collection methods and design methods to create and design information systems that are appropriate and effective as desired. The results achieved are the Administration Information System for Incoming and Outgoing Letters at Madrasah Tsanawiyah Univa Medan to simplify and improve the performance of employees who take care of mail management. In conclusion, managing incoming and outgoing mail is very important to improve performance and make it easier to find mail information. The data is presented and processed and presented using analytical methods